Tracer Study on the Graduates of Master of Arts in Education Program of Tomas Claudio Colleges - De Rosas , Eva; Beringuel, Julieta; Perez, Kristel Mary (International Journal of Sustainability and Advanced Integrated Research, 2026)
This tracer study examined graduates of the Master of Arts in Education (MAEd) program at Tomas Claudio Colleges from School Year 2010–2011 to 2019–2020. Using quota sampling and a descriptive survey design, data were collected through a researcher-made questionnaire checklist. Results show that most graduates are 31 years old and above, female, and single, teaching in public schools with permanent appointments. The majority have held their positions for 5–9 years, earning ₱30,000 or more per month. Age was significantly associated with employment status, while sex and civil status were not. Graduates reported that the MAEd program substantially contributed to their personal and professional development, and expressed high satisfaction with the curriculum, instruction, faculty, and program delivery, regardless of age, sex, or civil status. The study concludes that the MAEd program effectively supports graduates’ professional and personal growth, with employment outcomes influenced by age but not by sex or civil status. Overall, graduates are highly satisfied with the program, highlighting its value in preparing competent education professionals.